Batch and Continuous Flow Adsorption of Phenolic Compounds from Olive Mill Wastewater: A Comparison between Nonionic and Ion Exchange Resins. (23rd August 2016) - Pinelli, Davide; Molina Bacca, Aurora Esther; Kaushik, Ankita; Basu, Subhankar; Nocentini, Massimo; Bertin, Lorenzo; Frascari, Dario
Abstract : The goals of this work were (i) to compare two anion ion exchange resins (IRA958 Cl and IRA67) and a nonionic resin (XAD16) in terms of phenolic compounds adsorption capacity from olive mill wastewater and (ii) to compare the adsorption capacity of the best resin on columns of different length. The ion exchange resins performed worse than nonionic XAD16 in terms of resin utilization efficiency (20% versus 43%) and phenolic compounds/COD enrichment factor (1.0 versus 2.5). The addition of volatile fatty acids did not hinder phenolic compounds adsorption on either resin, suggesting a noncompetitive adsorption mechanism. A pH increase from 4.9 to 7.2 did not affect the result of this comparison. For the best performing resin (XAD16), an increase in column length from 0.5 to 1.8 m determined an increase in resin utilization efficiency (from 12% to 43%), resin productivity (from 3.4 to 7.6 g s o r b e d     p h e n o l i c s / k g r e s i n ), and phenolics/COD enrichment factor (from 1.2 to 2.5). An axial dispersion model with nonequilibrium adsorption accurately interpreted the phenolic compounds and COD experimental curves.